Airway responsiveness to mannitol in asthma is associated with chymase‐positive mast cells and eosinophilic airway inflammation. Issue 2 (February 2016) - Sverrild, A.; Bergqvist, A.; Baines, K. J.; Porsbjerg, C.; Andersson, C. K.; Thomsen, S. F.; Hoffmann, H. J.; Gibson, P.; Erjefält, J. S.; Backer, V.
Summary: Background: Airway hyperresponsiveness (AHR) to inhaled mannitol is associated with indirect markers of mast cell activation and eosinophilic airway inflammation. It is unknown how AHR to mannitol relates to mast cell phenotype, mast cell function and measures of eosinophilic inflammation in airway tissue. We compared the number and phenotype of mast cells, mRNA expression of mast cell‐associated genes and number of eosinophils in airway tissue of subjects with asthma and healthy controls in relation to AHR to mannitol. Methods: Airway hyperresponsiveness to inhaled mannitol was measured in 23 non‐smoking, corticosteroid‐free asthmatic individuals and 10 healthy controls. Mast cells and eosinophils were identified in mucosal biopsies from all participants. Mast cells were divided into phenotypes based on the presence of chymase. mRNA expression of mast cell‐associated genes was measured by real‐time PCR. Results: The proportion of submucosal MCTC was higher in asthmatic individuals with AHR to mannitol compared with asthmatic individuals without AHR (median: 40.3% vs. 18.7%, P = 0.03). Increased submucosal MCTC numbers were associated with increased levels of mRNA for thymic stromal lymphopoietin (TSLP) and CPA3 in asthmatics. Reactivity to mannitol correlated significantly with eosinophils in submucosa ( r (s): 0.56, P = 0.01). Conclusion: Airway hyperresponsiveness to inhaled mannitol is associated with an altered submucosal mast cell profile in asthmatic individuals. This mast cell profile is associated with increased levels of TSLP and CPA3. The degree of AHR to mannitol is correlated with the degree of eosinophilic inflammation in the airway submucosa.